Sub‐10 nm Features Obtained from Directed Self‐Assembly of Semicrystalline Polycarbosilane‐Based Block Copolymer Thin Films. (10th November 2014) - Aissou, Karim; Mumtaz, Muhammad; Fleury, Guillaume; Portale, Giuseppe; Navarro, Christophe; Cloutet, Eric; Brochon, Cyril; Ross, Caroline A.; Hadziioannou, Georges
<x xml:space="preserve">Abstract</x> Highly‐ordered arrays with sub‐10 nm features are produced with topographical‐directed self‐assembly of low‐molecular‐weight poly(1, 1‐dimethyl silacyclobutane)‐block‐poly(methyl methacrylate). This system turns out to be of high interest for lithographic applications since the domain orientation is solely controlled through the polymer layer thickness, while the promotion of the microphase separation is obtained by a short thermal annealing process under mild conditions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>